The Assessment of COVID-19 Effect on European Union Industrial Sector - Maria-Daniela TUDORACHE; Tamara Maria NAE; Ionuț JIANU (Communications of International Proceedings, 2021)
In this paper, we estimated the impact of COVID-19 shock on the industrial production and on the confidence in industry at European Union level, using Panel EGLS method - weighted by Cross-section SUR option. The negative impact we found on both indicators is quite high and may severely affect the economy, in the absence of political support and in the case of prolonging COVID-19 crisis or starting another lockdown waves. The largest drops of industrial production were found in Italy, Slovakia, Romania and Hungary, while Latvia, Malta, Finland and the Netherlands were less vulnerable to the COVID-19 shock. Through this paper, we also identified a high similarity between the dynamics of industrial production and the industrial confidence index. The outlooks are still exposed to uncertainty, but these have been improved in the latest months.
Keywords: industrial production; crisis; coronavirus; COVID-19; confidence.